Analysis of Movement and Music Characteristics of Performance Art in “Touching the Heart for a Broken Wing” Performance - Rochbeind, Fenny; Pristiati, Tutut (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
Research related to performance art in Indonesia has been carried out but has not been studied in-depth, and the topics are different from those analyzed by researchers. This study aims to describe the characteristics of motion and music and to know the relationship between the actions of the performer’s body in the performance. Qualitative methods were used in this study with an interdisciplinary approach. Data sources are obtained from performers and audiences, while data collection techniques are through observation, interviews, and documentation. Data analysis used RoseLee Goldberg’s performance art theory. These findings include 1) the characteristics of the performer’s body movements spontaneously visualizing gross and fine movements that are artistically related to music and other elements, and 2) the characteristics of music that spontaneously accompanies the performer’s body movements. The benefits of research on the performance art of “Touching the Heart for a Broken Wing” can be understood and appreciated by the public as a new form of art that provides new value to the art treasures in Indonesia.